Didactic proposal for the design of an intervention process in School Counseling (Innovaciones Educativas, 2022)
This essay introduces a didactical proposal for elaborating intervention processes in socio-educational counseling by considering the authors teaching experience during the years 2016 and 2019 in the courses Professional Practice I OE-2041 and Professional Practice II OE-2045, at Universidad de Costa Rica. The Counselling Study programs of the Ministry of Public Education were also considered. An analysis of why the counseling intervention is procedural is carried out based on five basic premises for the intervention. Likewise, this proposal integrates, for its understanding, dimensions, stages, and learning objectives that are presented sequentially. Therefore, it is concluded that the theoretical-methodological proposal is an innovative resource for both professionals in guidance and students of this program to understand counseling intervention as a process.
Keywords: counseling; pedagogical counseling; teaching practice; teaching process; teacher training; education